A preliminary phylogeny of the Palearctic naked-toed geckos (Reptilia: Squamata: Gekkonidae) with taxonomic implications - Bauer, Aaron M.; Masroor, Rafaqat; Titus-Mcquillan, James; Heinicke, Matthew P.; Daza, Juan D.; Jackman, Todd R. (Zootaxa, 2013)
Palearctic naked-toed geckos are a group of gekkonid geckos that range from North Africa to northern India and western China, with their greatest diversity in Iran and Pakistan. Relationships among the constituent genera remain incompletely resolved and the monophyly of key genera remains unverified. Further, competing classifications are in current use and many species have been allocated to different genera by different authors. We used both mitochondrial (ND2) and nuclear genes (RAG1, PDC) to explore relationships among representatives of all but one genus in the group (Rhinogecko), including four genera not previously included in phylogenetic analyses (Asiocolotes, Altigekko, Indogekko, and Siwaligekko). Siwaligekko (and presumably other Tibeto-Himalayan species often referred to Cyrtopodion) are more closely related to tropical Asian Cyrtodactylus than to Palearctic naked-toed geckos. Sampled species of Asiocolotes and Altigekko are sister taxa, but both genera are here considered junior subjective synonyms of Altiphylax. Cyrtopodion sensu lato is non-monophyletic; Mediodactylus and Tenuidactylus, which have variably been considered as subgenera or synonyms of Cyrtopodion are both valid genera. Indogekko is embedded within Cyrtopodion and is here treated as a subgenus. Bunopus and Crossobamon are closely related to one-another, and with Agamura are interdigitated among taxa previously assigned to Cyrtopodion. Our data confirm the previous identification of a Saharo-Arabian Stenodactylus/Tropiocolotes/Pseudoceramodactylus clade and verify that Microgecko and Alsophylax are not members of the main clade of Palearctic naked-toed geckos. Osteological differences between Tropiocolotes and Microgecko, formerly treated as congeneric, are discussed and illustrated. The divergence between Cyrtodactylus and the Palearctic naked-toed clade predates the initial collision of the Indian and Eurasian plates, but deeper divergences within both groups are consistent with mountain building in the Himalayas and adjacent ranges as promoting cladogenic events. Miocene divergences within Tenuidactylus are consistent with vicariant speciation caused by uplift events in the Iranian and Transcaspian regions. Taxonomic implications of our phylogenetic results are discussed and a preliminary allocation of all species of padless Palearctic gekkonids to genus is provided.